CONSTRUCTIVISM OF WOMEN'S COMMUNITY HIGHER EDUCATION IN PULOSARI VILLAGE, JOMBANG - Umi Hanik (Jurnal Analisa Sosiologi, 2022)
This study aims to look at the constructivism of the Pulosari community towards women with higher education, and the process of forming constructivism in the community regarding education. Higher education is not gender-biased, men or women have the same opportunities in higher education. However, the narrative in the grassroots community, especially in Pulosari, is that the community considers higher education for women to be the same as women in general, both in structural positions in society and at the work level. This study uses a qualitative method, with a phenomenological approach, and data is obtained through observation and interviews. The results of this study are, the constructivism of highly educated women in the Pulosari community is caused by first, the understanding of the position of women narrated in the colonialism era, the second society questions the function of higher education for women in the world of structure, the third knowledge of education in the family and the last is women constructed in the form of macak, masak, and manak.Keywords: Constructivism, Women, Higher Education AbstrakPenelitian ini bertujuan untuk melihat konstruktivisme masyarakat Pulosari terhadap perempuan dengan pendidikan tinggi, dan proses pembentukan konstruktivisme di masyarakat mengenai pendidikan. Pendidikan tinggi tidak bias gender, laki-laki atau perempuan memiliki kesempatan yang sama dalam pendidikan tinggi. Namun narasi di masyarakat akar rumput, khususnya di Pulosari, masyarakat menganggap pendidikan tinggi bagi perempuan sama dengan perempuan pada umumnya, baik dalam posisi struktural di masyarakat maupun di tingkat pekerjaan. Penelitian ini menggunakan metode kualitatif, dengan pendekatan fenomenologis, dan data diperoleh melalui observasi dan wawancara. Hasil penelitian ini adalah, konstruktivisme perempuan berpendidikan tinggi di masyarakat Pulosari disebabkan oleh pertama, pemahaman tentang kedudukan perempuan yang dikisahkan pada era kolonialisme, kedua masyarakat mempertanyakan fungsi pendidikan tinggi bagi perempuan dalam dunia pendidikan. struktur, ketiga pengetahuan pendidikan dalam keluarga dan yang terakhir adalah perempuan yang dikonstruksi dalam bentuk macak, masak, dan manak.Kata kunci: Konstruktivisme, Perempuan, Pendidikan Tinggi